Development of a prototype handmade water filter / Muhammad Danish Fathullah Mohamad Zaidy - Mohamad Zaidy, Muhammad Danish Fathullah (2024)
This project aims for people with low budgets to be able obtain a good water filter without using a lot of cost. The objectives of this project are to design and fabricate a low-cost water filter within a budget of RM250, which is more convenient for most people. There are a lot of existing products which are most of them are not relevant and overpriced. By utilizing most of the components such as UV lights, pump and advanced design principles, the prototype handmade water filter fills with a promising result which is having clean water to use for cooking and drinking. The project will employ a design-based approach, encompassing research, conceptualization, prototyping, and testing. The project also gives a clean water and safe for consumers to consume the water. The water dispenser also having a complex route for the clean water to flow, but after it revised and testing, the outcome of the filters are unexpectedly good.